A photo-triggered antifungal nanoplatform with efflux pump and heat shock protein reversal activity for enhanced chemo-photothermal synergistic therapy. (16th April 2021) - Yang, Dongliang; Tu, Yuexing; Wang, Xiaorui; Cao, Changyu; Hu, Yanling; Shao, Jinjun; Weng, Lixing; Mou, Xiaozhou; Dong, Xiaochen
Abstract : A photo-triggered release antifungal platform with efflux pump and heat shock protein reversal activity was developed to enhance chemo-photothermal synergistic therapy. Abstract : Drug-resistant pathogens are less sensitive to traditional antibiotics in many stubborn infections. It is imminently desirable to have an effective alternative therapeutic agent for combating drug-resistant pathogen infections. Herein, a photo-triggered multifunctional nanoplatform (TMOB/FLU@PCM NPs) with efflux pump and heat shock protein expression reversal activity is developed for the highly effective eradication of drug-resistant fungi. Upon 808 nm laser excitation, the hyperthermia originating from a BODIPY derivative (TMOB) can not only melt the phase-change material (PCM) vehicle consisting of hexadecanol and cis -2-dodecenoic acid (BDSF) to on-demand release the quorum sensing molecule BDSF and the antifungal drug fluconazole (FLU), but can also destroy the integrity of the C. albicans cell membrane. Thanks to the release of BDSF from TMOB/FLU@PCM NPs, the expression of drug efflux pumps ( MDR1, CDR2, CDR4 ) and thermotolerant proteins ( HSP12, HSP21, HSP60, HSP90 ) is inhibited, which further boosts the therapeutic effect of chemo/photothermal therapy. Moreover, the hyphal and biofilm formation of C. albicans can be blocked by TMOB/FLU@PCM NPs under 808 nm laser irradiation. In vitro and in vivo results indicate that TMOB/FLU@PCM NPs with good biosafety can efficiently eliminate clinical azole-resistant C. albicans . Thus, TMOB/FLU@PCM NPs exhibits a promising future in the treatment of azole-resistant C. albicans infection.